Establishment of wildflower strips in a wide range of environments: a lesson from a landscape‐scale project. Issue 4 (20th September 2021) - Stroot, Lukas; Brinkert, Annika; Hölzel, Norbert; Rüsing, Alina; Bucharova, Anna
Abstract : Wildflower strips established on arable fields or intensively used grassland are an important tool for supporting biodiversity in impoverished landscapes. They provide ecosystem services like resources for pollinators, and, if they are based on perennial native plants, also plant diversity as well as nesting and wintering habitats for insects. To successfully create such wildflower strips, it is important to understand parameters that restrain establishment of the target plant species. Here we studied initial plant establishment at 45 experimental plots located in recently established wildflower strips across a broad variety of environmental conditions, complemented by 32 control plots in adjacent intensively used grasslands. All strips were seeded with a nearly identical seed mixture of native species, and thus, differences in vegetation were largely driven by environmental factors. We recorded vegetation and related it to soil parameters, seeding season, and previous use. Establishment of wildflower strips nearly doubled plant species richness in comparison with adjacent grasslands. Seeded species established better on former arable land than in intensively used grasslands, but also in grasslands, nearly half of the species from the seed mixture established. Sown species were more abundant in wildflower strip seeded in fall. The success of the seeded species was largely independent of soil parameters. In summary, the initial establishment of perennial wildflower strips is likely to be successful in a wide range of soil conditions, but further monitoring is needed to understand the vegetation development over the whole time period these strips are supposed to persist for.